Electronic transference assessment of the redox processes at carbon electrodes coated with Geobacter sulfurreducens that grown at different temperatures - Peixoto, L. (2011)
In the present study, the kinetic parameters of redox reactions and the proteomic profiles of Geobacter sulfurreducens grown at different temperatures (25 ºC and 37 ºC) were evaluated. Oxidation peaks with different potentials and current intensities were observed for both cultures. Also, the outer membrane proteins of the bacteria at the two temperatures revealed different profiles that can be responsible for different redox centers. Thus, G. sulfurreducens that grows at different temperatures may express different cytochromes in the external membrane.